Combating Social Exclusion Faced by Disabled People in the Wage Labour Market in Hong Kong. Issue 4 (8th August 2017) - Chau, Ruby C. M.; Yu, Sam W. K.; Boxall, Kathy
Abstract : This article contributes to the search for suitable approaches to combat social exclusion faced by disabled people in capitalist wage labour markets. Referring to policy and service examples in Hong Kong, it reviews four social exclusion approaches – the Moral Underclass (MUD), Social Integrationist (SID), Redistributive (RED) and Collective Production (COP) approaches. These approaches are explored in relation to three key issues: (1) the diverse preferences of disabled people; (2) the myth of infeasibility regarding unconventional approaches and (3) the defects of the medical model of disability. The article argues that the MUD and SID approaches are more associated with the medical model of disability and emphasise individual changes. The RED and COP approaches contain more features of the social model of disability and are in favour of social and structural changes. The COP approach stresses the diverse preferences of disabled people and supports innovative services to combat social exclusion.